Investigation and Validation of the Scale of Students’ Readiness for Online Learning - Shayestehfar, Abbas; Pourasghar, Nasibe; Masoomifard, Marjan; Nouri, Ziba (Assessment and Practice in Educational Sciences, 2026)
The objective of this study was to investigate university students’ level of readiness for online learning and to validate the psychometric properties of the Online Learning Readiness Scale in the context of distance education. This correlational study employed confirmatory factor analysis to assess the structure and validity of the Online Learning Readiness Scale. The statistical population included 1,930 undergraduate students of educational sciences enrolled in online classes at Payam Noor University in Hormozgan Province during the 2021–2022 academic year. Based on the Krejcie and Morgan table and anticipating potential non-response in online surveys, 346 students ultimately completed the questionnaire distributed via WhatsApp and email. The instrument consisted of 18 items measuring five dimensions: internet/computer self-efficacy, self-directed learning, learner control, motivation to learn online, and online communication self-efficacy. Validity was assessed through face, content, convergent, discriminant, and concurrent validity procedures, and reliability was evaluated using Cronbach’s alpha and composite reliability. Data analysis was performed using SPSS (chi-square, t-test, ANOVA) and PLS software. Confirmatory factor analysis supported the five-factor structure of the scale, with all factor loadings exceeding 0.48 and t-values surpassing ±1.96, indicating acceptable reliability and construct validity. AVE values were above 0.48 for all constructs, and discriminant validity was confirmed through the square root of AVE method. Students demonstrated high readiness in self-directed learning, motivation, and internet/computer self-efficacy, while showing lower readiness in online communication self-efficacy and learner control. No significant differences were observed in readiness across gender, age, academic year, employment status, daily internet use, or course type. Several structural paths were confirmed, particularly the relationships between internet/computer self-efficacy and self-directed learning, learner control, and motivation. The Online Learning Readiness Scale demonstrated satisfactory validity and reliability, and the findings highlight the need to strengthen students’ communication self-efficacy and learner control for more effective online learning.